STRENGTHENING THE ROLE OF CONSULTING SERVICES IN REFORMING THE UZBEKISTAN ECONOMY IS A REQUIREMENT - Kholbutaeva Shakhnoza Abduvalievna (Research Parks Publishers, 2021)
The article examines the foreign experience in the development of innovative consulting services, the evolution of service entrepreneurship in Uzbekistan and the peculiarities of the formation of the market of consulting services. The article considers the need to create a model of professional qualities, knowledge and skills that reflects the specifics of the work of consultants providing services and to create a special model necessary for a specialist